Features prevalence of polymorphism lle50Val gene IL4RA in patients with bronchial asthma and healthy children school age Vinnichina - Dudnyk, V. M.; Kutsak, O. V. (Journal of Education, Health and Sport, 2017)
Today, the mechanism of development of bronchial asthma (BA) is interpreted from the molecular-genetic point of view, taking into account the polymorphism of genes that affect the formation and clinical manifestations of it. Studying the genetic aspects of bronchial asthma in children is aimed at studying various associations of polymorphisms of genes of interleukin ligands and their receptors. The aim - to evaluate the prevalence of genotypes and alleles for the gene polymorphism lle50Val IL4RA in patients with asthma and healthy school children Vinnitsa region. Materials and methods. We examined 75 children of school age, patients with atopic bronchial asthma and 25 practically healthy children aged 6 to 18 years living in Vinnitsa region. The genotyping of IL4RA, SNP polymorphism lle50Val was carried out using a polymerase chain reaction (PCR). The odds ratio was calculated to determine the risk of developing asthma in carriers of various alleles and genotypes of the IL4RA gene. Results and discussion. Homozygous genotype A / A Vinnichiny among school children suffering from asthma occurs in 4.34 times (p <0,05) more often and genotype G / G - 4.2 times (p <0,05) less compared to practically healthy children with prevalence 1.6 times allele a carriers (p <0,05), respectively, carrier genotype a / a and a allele is associated with the development of asthma and is a marker of increased risk of disease, and the presence of the genotype G / G and allele G - "unfavorable" to the development of bronchial asthma. The distribution of the frequency of genotypes for the Ile50Val polymorphism of the IL4RA gene is independent of sex and indicates a collision lshennya heterozygous genotype A / G patients among boys in 1.84 times, and among girls - by 1.3 times compared with native homozygous genotype A / A (p <0,001) and, respectively, 8.74 and 9 times - compared with a mutant genotype G / G (p <0.001). Conclusions. Established that the carrier genotype A / A and A allele asootsiyuyetsya with the development of asthma and the presence of the genotype G / G and G alleles can be considered a factor that affects the "unfavorable" development of asthma in children of school age.